REACT Learning on the Topic of Elasticity to Enhance Students' Analytical Abilities - Dea Safira; Abdul Salam; Dewi Dewantara (Jurnal Ilmiah Pendidikan Fisika, 2023)
Conventional learning in class so far has not been maximized to train students' analytical abilities. One of the lessons that can improve students' analytical skills is contextual learning, one of which is REACT (Relating, Experiencing, Applying, Cooperating, Transferring) learning. Therefore, further research is needed on REACT learning to improve students' analytical abilities. This study aims to describe the effectiveness of REACT learning on elasticity to improve students' analytical abilities. This research is a pre-experimental design with one group pre-test and post-test. The subjects of the research trial were 29 students of class XI MIPA 2 SMA Negeri 10 Banjarmasin. Data collection techniques in this study used student learning outcomes tests. Furthermore, research data analysis techniques are carried out by calculating N-gain based on student learning outcomes tests. The results showed that the effectiveness of REACT learning based on N-gain calculations was 0.74 in the high category. So, it can be concluded that REACT learning is effective and feasible for improving students' analytical abilities. This proves that the use of REACT learning plays an important role in improving students' analytical abilities and assisting the development of more effective and innovative learning methods.